(untitled) (PerCursos, 2022)
The diversity of the landscape and, therefore, of the geomorphological features is certainly what makes the territory covered by the Caminhos dos Cânions do Sul Geopark, RS/SC (GCCS) unique. Marked by the strong compartmentalization of the landscape by the presence of a large escarpment, it encompasses different geomorphological units whose characteristic features constitute geomorphosites of local and international relevance. Geomorphosites in this territory have values such as aesthetic, ecological, historical-cultural and mainly scientific. The aim of this paper is to characterize the sites of geomorphological interest in the Caminhos dos Cânions do Sul Geopark (RS/SC), based on the inventory made for its implementation. There are 30 official geosites in the GCCS and those whose relevant content is the geomorphological nature were selected. They were grouped into four categories of geomorphosites: (i) canyons, (ii) waterfalls, (iii) witness hills and (iv) coastal and marine. Recognising the value of these geomorphosites will certainly expand the bases for the definition of geotourism strategies, as well as stimulate the geoconservation and the promotion of the geoheritage.